Biochemical and Spectroscopic Characterization of a Recombinant Laccase from Thermoalkaliphilic Bacillus Sp. Fnt with Potential for Degradation of Polycyclic Aromatic Hydrocarbons (Pahs) - Zuniga-Navarro, G; Aliaga-Vidal, C; Aliaga-Vidal, C; Cortés-Antiquera, R; Blamey-Alegria, J (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Laccases are industrially relevant enzymes that are known for the wide variety of substrates they can use. In recent years, fungal laccases have been progressively replaced by bacterial laccases in applied contexts due to their capacity to work on harsh conditions including high temperatures, pHs, and chloride concentrations. The focus of researchers has turned specifically towards enzymes from extremophilic organisms because of their robustness and stability. The recombinant versions of enzymes from extremophiles have shown to overcome the problems associated with growing their native host organisms under laboratory conditions. In this work, we further characterize a recombinant spore-coat laccase from Bacillus sp. FNT, a thermoalkaliphilic bacterium isolated from a hot spring in a geothermal site. This recombinant laccase was previously shown to be very active and thermostable, working optimally at temperatures around 70–80 °C. Here, we showed that this enzyme is also resistant to common inhibitors, and we tested its ability to oxidize different polycyclic aromatic hydrocarbons, as these persistent organic pollutants accumulate in the environment, severely damaging ecosystems and human health. So far, the enzyme was found to efficiently oxidize anthracene, making it a compelling biotechnological tool for biocatalysis and a potential candidate for bioremediation of aromatic contaminants that are very recalcitrant to degradation. © 2023 by the authors.